The afterlife of Moses : exile, democracy, renewal - Steinberg, Michael P. (Cultural memory in the present, 2022)
"In The Afterlife of Moses, Steinberg addresses the story of Moses and the Exodus as a foundational myth of politics, of the formation not of a nation but of a political community grounded in universal law. Motivated in part by this recent period of reactionary insurgency in the US, Europe, and Israel, this work of intellectual history articulates the way in which a critique of myths of origin as a principle of democratic government, affect, and citizenship has equal relevance in these places and equal fragility"--
Keywords: myytit; Raamattu; kristinusko; juutalaiset; poliittinen filosofia; poliittinen historia : Amerikan yhdysvallat; poliittinen historia : Israel